Pengembangan Media Kartu Huruf Angka Bergambar (HABER) dalam Pengembangan Kemampuan Kognitif Anak Usia Dini - Fadhilah Afifah (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aimed to develop and evaluate the feasibility of the Pictorial Letter and Number Card (HABER) media in supporting the cognitive development of early childhood learners. The study employed a Research and Development (R&D) approach using the 4D model, which consists of the define, design, develop, and disseminate stages. The research was conducted at TK Khalifah III Makassar involving four kindergarten teachers as research participants. Data were collected through observation, interviews, questionnaires, and expert validation sheets. The data were analyzed using descriptive quantitative and qualitative techniques to determine the validity, practicality, and effectiveness of the developed product. The findings revealed that teachers needed innovative learning media and practical guidebooks to support cognitive learning activities. The HABER media developed in this study consists of letter cards, number cards, picture cards, and a user guidebook designed according to children’s developmental characteristics. Expert validation results indicated that the media met the criteria of validity. Furthermore, the practicality test showed a score of 92.86%, while the effectiveness test reached 94.9%, both categorized as very high. These findings demonstrate that HABER is a valid, practical, and effective learning medium that can facilitate cognitive development in early childhood. Therefore, HABER can be used as an alternative instructional medium to support meaningful and engaging learning experiences in early childhood education